Conjugate heat transfer analysis for forced convective flow through a parallel plate microchannel: Effect of nonuniform asymmetric heating. (23rd July 2021) - Borah, Abhijit; Pati, Sukumar; Baranyi, László
Abstract: We analyze numerically the influence nonuniform asymmetric heating on the forced convective conjugate heat transfer characteristics for two-dimensional, steady flow of Newtonian fluid through a parallel plate microchannel. A parametric study is carried out by varying the phase difference, amplitude and period of fluctuation of the imposed heat flux, thickness and thermal conductivity of the walls as well as Reynolds number in the range of 25–600. Results reveal that there exists a complex interaction between the imposed heat flux profile and the physico-thermal properties of the walls in altering the thermal transport characteristics. The impact of asymmetric heating in altering the overall thermal transport rate is greater than the effect of nonuniform heating.